The SO2 allowance trading system and the clean air act amendments of 1990: Reflections on twenty years of policy innovation - Gabriel Chan; Robert Stavins; Robert Stowe; Richard Sweeney (Fondazione Eni Enrico Mattei (FEEM), 2012)
The introduction of the U.S. SO2 allowance-trading program to address the threat of acid rain as part of the Clean Air Act Amendments of 1990 is a landmark event in the history of environmental regulation. The program was a great success by almost all measures. This paper, which draws upon a research workshop and a policy roundtable held at Harvard in May 2011, investigates critically the design, enactment, implementation, performance, and implications of this path-breaking application of economic thinking to environmental regulation. Ironically, cap and trade seems especially well suited to addressing the problem of climate change, in that emitted greenhouse gases are evenly distributed throughout the world's atmosphere. Recent hostility toward cap and trade in debates about U.S. climate legislation may reflect the broader political environment of the climate debate more than the substantive merits of market-based regulation.
Keywords: Q52; Q55; Q58; 330; Cap-and-Trade; Market-Based Environmental Policy; Acid Rain; Sulfur Dioxide; Clean Air Act Amendments; Umweltbelastung; Saurer Regen; Schwefel; Umweltpolitik; USA